Design Tourism Industry in Era of Society 5.0 through Blockchain Technology - I Gede Agus Krisna Warmayana; Sri Sulistyawati Anton (IAHN-TP Palangka Raya, 2022)
In the era of society 5.0, Cyber-physical systems or intelligent systems are integrated and distributed online computer systems that are useful in various sectors, one of which is the tourism industry. In the development of the tourism industry and its problem, blockchain as information technology can be utilized to help solve this problem and build sustainable tourism globally. However, the challenge for blockchain adoption in the tourism industry is a new technology with a different concept from the existing system. Therefore, the purpose of this study is to design the use of blockchain technology to improve the tourism industry so that it has a positive impact on the tourism industry in terms of trust, transparency, and security by applying 4 blockchain concepts, including Type blockchain, Storage structure, Layers, Transaction Model using quantum computing